Sm3+ ions doped zinc barium tellurite oxyfluoride glasses for laser materials - Yamsuk, Y; Yasaka, P; Kaewkhao, J; Sangwaranatee, N (Journal of Metals, Materials and Minerals, 2020)
The Sm3+ ions were doped tellurite glasses with composition (55-x) TeO2-10ZnF2-35BaO-xSm2O3 (where x = 0.00, 0.05, 0.10, 0.50, 1.00 and 1.50 in mol%) to investigate the physical, the optical, the luminescence and structural properties. The functional groups can be identified using FT-IR spectra of Sm3+ in the glasses. The most intense peak from emission spectra is at 600 nm (4G5/2->6H7/2) corresponding to reddish-orange color. The oscillator strengths were resolved from the absorption spectra and then used to calculate the Judd–Ofelt (J–O) intensity parameters. The radiative properties were calculated by J–O intensity parameters for various transitions in tellurite glass matrices. According to the results of stimulated emission cross section, lifetime and the branching ratio of the emission transition 4G5/2->6H7/2, it is promised that 0.50 mol% of Sm2O3 doped tellurite glasses is the potential laser material.